High expression of the aspartate–glutamate carrier Aralar1 favors lactate consumption in CHO cell culture. (April 2013) - Zagari, Francesca; Stettler, Matthieu; Baldi, Lucia; Broly, Hervé; Wurm, Florian M; Jordan, Martin
Process performance of mammalian cell cultures can be strongly impacted by high lactate accumulation, which can be a clone or media-dependent characteristic. In this study, the expression of specific genes was measured in several Chinese hamster ovary cell lines under culture conditions leading to different lactate profiles. A reduced expression of two genes was observed under conditions of high lactate accumulation: AGC1/Aralar1, a member of the malate–aspartate shuttle (MAS) and Timm8a1. Overexpression of either of these two genes in the lactate-producing cell line diminished lactate accumulation. This was achieved by promoting a metabolic switch to lactate consumption after day 6, while maintaining a glycolytic rate similar to the parental cells. On the other hand, the biochemical inhibition of MAS activity increased lactate accumulation. All together, these results indicate MAS as a key factor to promote a shift to lactate consumption in cultivated Chinese hamster ovary cells.